1993
DOI: 10.1002/ddr.430280104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the complexation of various fentanyl analogs in hydroxypropyl‐β‐cyclodextrin after epidural and intrathecal administration in rats

Abstract: Complexation of various equipotent doses of fentanyl-like opioids in hydroxypropyl-6-cyclodextrin (HP-P-CD) results in a potentiation of the spinal activity of these opioids after both epidural and intrathecal administration in a fixed diluent volume o f 10 p,l. The first active and most optimal concentrations of HP-(3-CD after epidural administration differed between the opioids and varied from 1 to 20% HP-P-CD. The duration of deep surgical analgesia increased at optimal concentrations of HP-P-CD with a fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The effects of HP--CD in altering the activity of a number of opioids and model drugs after intracerebral, intrathecal, and epidural administration have been mixed. [94][95][96][97][98][99] The results indicated that the effects of HP--CD varied with concentration. No dramatic long-term sustaining effect was observed in any of the studies although some interesting observations were made.…”
Section: Parenteral Applications Of Cyclodextrinsmentioning
confidence: 97%
“…The effects of HP--CD in altering the activity of a number of opioids and model drugs after intracerebral, intrathecal, and epidural administration have been mixed. [94][95][96][97][98][99] The results indicated that the effects of HP--CD varied with concentration. No dramatic long-term sustaining effect was observed in any of the studies although some interesting observations were made.…”
Section: Parenteral Applications Of Cyclodextrinsmentioning
confidence: 97%
“…A retinal−dextran conjugate solubilized by β-cyclodextrin was reported to be less cytotoxic and retained the ability to inhibit the growth of cancer cells . 2-Hydroxypropyl-β-cyclodextrin serves as a benign vehicle for the delivery of drugs which are directed at sites in the central nervous system. , When opioids were administered intrathecally in rats, 2-hydroxypropyl-β-cyclodextrin prolonged the duration of analgesia and reduced the supraspinal side effects such as the incidence of catalepsy and blockade of the pinna reflex. 2-Hydroxypropyl-β-cyclodextrin appears to provide a slow release reservoir, diminishing the redistributional loss of spinally administered drug from the locus of desired effect to systemic circulation and extraspinal tissues.…”
Section: Systemic Detoxicationmentioning
confidence: 99%